Crystal engineering studies of metal 1,1ï¿½-dithiolates: coordination polymers and beyond / Tan Yee Seng - Tan, Yee Seng (2016)

(untitled)
Crystal engineering was implemented by conducting three distinctive projects, covering a total of 22 compounds. These compounds were fully characterised via various spectroscopic techniques and materials analysis, including FT-IR, UV-Vis, PL, SCXRD, PXRD, NMR, TGA, DSC and CHN elemental analysis. Crystallographic study of all compounds forms the core focus of current research for delineation of crystal engineering. The first project assessed seven crystal structures of same metal centre and ligand, with two forming one-dimensional coordination polymers. The factors leading to formation of solvomorph and supramolecular isomers were investigated. Solvomorph were obtained from different crystallisation parameters and solvent systems, while unanticipated non-reversible single crystal to single crystal transformations were found to afford two pairs of supramolecular isomers (1 to 2 and 6 to 7), stimulated by stabilisation energy in crystal systems and atmospheric moisture. The above ï¿½non-reversible transformationsï¿½ were, however interconverted by developing a solvent-induced reversible transformation system. Hexamethylenetetramine, a multidentate linker, was employed in the second project, which revealed its adoption of multiple coordination modes through the complexation with different cadmium xanthates. Unexpectedly, the coordination mode of hexamethylenetetramine was not affected despite varying the mole ratio of linker and precursor, i.e. 1:1, 1:2, and 2:1, identical adducts were obtained in respective synthesis. Hexamethylenetetramine functioned as ?2 and ?3 to form one-dimensional coordination polymers in compound 8 and 9, and ?1 in the dimeric motif of compound 10. The coordination modes of hexamethylenetetramine depend upon the orientation of cadmium xanthate in the molecule, as demonstrated by compounds 8 and 9. The highly packing crystal system of compound 8 oriented the methyl group of xanthate which prevented the coordination of third nitrogen atom of hexamethylenetetramine; while the steric effect iv induced by the ethyl group resulted in a position which allowed the third coordination of hexamethylenetetramine in compound 9. The third project aims to introduce the Cï¿½H????(PdS2C) interactions in palladium xanthate. Palladium xanthate 11 ï¿½ 22, a total of 12 compounds were prepared and the Cï¿½H????(PdS2C) interactions were successfully implemented in 11 out of 12 compounds, with some structures displayed up to a maximum of six interactions per molecule. Compound 13 was subjected to density functional theory calculations; the Cï¿½H????(PdS2C) was verified as second important interactions to support the respective crystal system, followed after Pd???S interactions. In addition to the above, the crystal system was also stabilised by hydrophobic interactions of side-by-side aliphatic chains.